An Exploration on the Role Digital Image Manipulation Plays in Fashion Magazines on the Perceptions of Physical Attractiveness of Black Women in S.A, According to the Social Constructionism Theory - Dunn, Germaine (The IIE, 2015)
“Retouching model portraits has become a standard, usually with the intent of enhancing the subject’s best features and minimizing their worst in fashion and magazine photography” (Reaves et al, 1990: 24). With South African black women being identified as the largest readership race percentage within True Love Magazine namely 96 % (Media 24, n.d.). The researcher aims to unpack the term digital image manipulation (retouching) within fashion magazines in relation to an individual’s perceived physical attractiveness. The purpose of this study is to determine if there is a link between digital image manipulation and physical attractiveness amongst Black South African women between the ages of 25 and 34 in South Africa using True Love Magazine as a case study. The research undertaken made use of qualitative research methods in the form of a field study including focus groups and unstructured in-depth interviews which were facilitated and guided by the researcher in order to answer the research questions. This study explored the role digital image manipulation plays in fashion magazines on the perceptions of physical attractiveness of black women in SA, according to the Social Constructionism theory. In conducting the study the researcher found that True Love has set an acceptable standard for women reading the magazine as the retouches are subtle and do not set unrealistic standards. Women can relate to the cover girls portrayed on the magazine as diverse women with various skin tones, hair styles such as natural hair, weaves, dread locks are used ensuring all African women are represented. Although the influence the magazine exerts is one of reference to fashion and make-up tips, True Love is seen as the epitome of black excellence for women as the celebrities or stars chosen are women that participants in the study aspire to be like. Women in the study were all aware of the magazine cover retouches and would be influenced if the covers were untouched as there is a certain expectation for the covers to be perfect and flawless. True Love merely represents what society has already constructed and what women find attractive and aspiring.
Keywords: Social Constructionism Theory; Fashion; Fashion Magazines